A Local Identity Breakdown: Locality and the State in Huizhou's Tax Controversy of 1577. (2nd January 2020) - Du, Yongtao
Abstract : The geographical scale of locality has never been clearly defined in the recent "localist turn" scholarship on late imperial China: "the local" there could refer to a county, a prefecture, and occasionally a region that contains more than one prefecture. One cause of this scalar inexactitude can be found in the intellectual trajectory of the local history orientation in Chinese studies. Another, probably more important cause is that historical actors themselves in the late imperial period kept the scale of locality fluid in their performances of local identity and their practices of local activism. Behind this fluidity may hide some crucial yet unexplored issues of both locality and localism in late imperial China. This article takes as an example the controversy over the "head tax on silk" (rending sijuan, 人丁絲捐) that broke out in the Huizhou (徽州) Prefecture in 1577 to illuminate the flexibility of scale in local identity formation, as well as the poverty of locality as a source of political loyalty.